Corporate Social Reporting Practices in India Special Bhilwara Industry: Understanding the Importance and Challenges of Social Audit in Corporate Reporting (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of “Social Audit” and accounting has been derived from the concept of “Corporate Social Responsibility” that is followed by corporate entities around the globe. It has become a popular tool to determine a company’s social impact in the community. It is a process by which an attempt is made to find out whether the benefits of the projectsactivities reach the people for whom it is meant. The objectives of social audit are – to look at what the social enterprise is doing, to evaluate how well public resources are being used to meet the real needs of target beneficiaries, to ascertain where improvements need to be made and what those improvements should be and to strengthen accountability and transparency in local bodies and many more. Generally Government and Funding Agencies, Private Enterprises and Civil society are the users of social audit. Social audit benefits disadvantaged groups, increases accountability, evaluates the fulfilment of social responsibility etc. The main difficulties in social audit are – absence of appropriate social accounting and reporting systems, mind-set of people and lack of education among the common masses. In this background, an attempt has been made in this paper to discuss the ins and outs of ‘Social Audit’.